Symbolic Interactionism among Employees of Different Ethnicities: A Descriptive Study of Intercultural Communication at Citibank Pondok Indah, South Jakarta (Oratio Directa, 2018)
Culture manifest itself in patterns and nature of forms of activity and behavior that serve as models for adjustment actions and communication styles which allow people to live in a certain level of technical development. Culture is sustainable and present everywhere; culture includes all affirmations of behaviors received during the life period. Culture is also recognized as form and structure form, physical form and social environment which influence how we can live. Each culture has its own way of moving, sitting, standing, lying, and making gestures, body language is culturally conditioned and should be interpreted according to the cultural background. It means, the understanding of a person’s attitude or action is only partially understood when it can cross the cultural barrier. In the new situations and it is not being understood in the process, we will depend heavily on the interpretation of nonverbal communication, the further the cultural differences, the greater the chance that we will make a wrong interpretation.
Keywords: Symbolic interaction; Communication among different culture; Language; Intercultural Communication; Culture